RELIGIÃO, IMIGRAÇÃO E GÊNERO: UMA ANÁLISE A PARTIR DE UMA CHAVE DE LEITURA FEMINISTA PÓS/DES COLONIAL SOBRE O FENÔMENO DO ASSOCIATIVISMO RELIGIOSO ENTRE MULHERES IMIGRANTES BOLIVIANAS BATISTAS NA CIDADE DE SÃO PAULO - CAMPANARO, PRISCILA KIKUCHI (2018)
The present work seeks to show how the religious associative contributes to the process of religious / theological re-signification of the immigrant women. From the observation of a considerable contingent of Bolivian immigrants who attend and lead evangelical churches in the city of São Paulo, Bolivian Through a field survey conducted at the First Hispanic Baptist Church (PIBHB), located in the city of São Paulo, in a focus group format (collective interviews), it was possible to collect data that had significant access to the history of migration and networks of meaning of these women, and also perform a Feminist Hermeneutics activity, where they read some biblical texts in which the main characters were women, shared the explanation, what they understood and the application of this text to life . The hypothesis of this thesis was based on the understanding that postcolonial feminism and decolonial feminism are important theoretical contributions to analyze the phenomenon of religious associativism and the theological / religious re-significations of these women in particular. The objective of this research was to articulate the data collected in the focus group research and to put them in dialogue with the assumptions of these two theoretical perspectives, using them as key reading and theoretical reference.